2001
DOI: 10.1159/000051785
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment in Two Cases of Steroid-Dependent Cutaneous Polyarteritis nodosa with Low-Dose Methotrexate

Abstract: To the best of our knowledge, only 3 cases of cutaneous polyarteritis nodosa (PAN) treated successfully with methotrexate (MTX) have been reported in the medical literature. We report 2 further cases of steroid-dependent cutaneous PAN treated successfully with low-dose weekly MTX therapy. The clinical and biological tolerance of MTX was excellent. The cutaneous lesions started to regress within 3 weeks. One of the patients reported full recovery which lasted 2 years after stopping the therapy. So, MTX seems to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…When there is a lack of response to standard treatment or concerns about possible steroid toxicity, intravenous immunoglobulin (IV-Ig) has been successfully used [110]. Some success has also been reported with methotrexate [111], colchicine and dapsone [112], cyclophosphamide [98], pentoxifylline [113] and chloroquine [114]. …”
Section: Cutaneous Polyarteritis Nodosamentioning
confidence: 99%
“…When there is a lack of response to standard treatment or concerns about possible steroid toxicity, intravenous immunoglobulin (IV-Ig) has been successfully used [110]. Some success has also been reported with methotrexate [111], colchicine and dapsone [112], cyclophosphamide [98], pentoxifylline [113] and chloroquine [114]. …”
Section: Cutaneous Polyarteritis Nodosamentioning
confidence: 99%
“…Some cases require administration of systemic corticosteroids 11. Intractable cases require immunosuppression with CYC, azathioprine or methotrexate 12. There is no anecdotal information available on treatment for relapses of CPAN.…”
Section: Discussionmentioning
confidence: 99%
“…[10] The exact duration of treatment is uncertain. Immunosuppressive agents such as cyclophosphamide, azathioprine, or methotrexate, can been used in cases unresponsive to steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive agents such as cyclophosphamide, azathioprine, or methotrexate, can been used in cases unresponsive to steroid therapy. [810] The non-steroidal anti-inflammatory (NSAIDs) drugs are used only in the milder form of CPAN, and antibiotics are used in cases of antecedent streptococcal throat infections. In cases resistant to systemic steroids and immunosuppressive therapy, studies have shown that intravenous immunoglobulin can be successfully used.…”
Section: Discussionmentioning
confidence: 99%